Rituals in gastrointestinal endoscopy at the crossroads of shaman and science - Sonnenberg, Amnon (Endoscopy International Open, 2017)
Background and aim Over the last decades, the length of time required for endoscopic procedures has greatly expanded. The aim of the present decision analysis is to study the interactions amongst various factors that have caused such delays and to compare the relative magnitude of their influences.Methods Performance of gastrointestinal endoscopy is influenced by the interaction of five domains, that is, (1) patient discomfort and fear; (2) injury, disorder, and disruption; (3) rituals to reduce fear, prevent disruption, and maintain order; (4) administrators or various health providers carrying out a ritual; (5) information, knowledge, and science, which influence fear, prevent disruption, and curtail unnecessary ritualistic behavior. A Markov chain model is used to describe the interaction among the five domains.Results Overall, science exerts the strongest influence, followed by fear and ritual as distant second and third most relevant influences, respectively. Disruption and administrator exert only a minor influence on the system of mutual interactions.Conclusions Studying patterns of ritualistic behavior during endoscopy and subjecting them to means of scientific research could help eliminate redundancy, cutting unnecessary rituals, and thus making gastrointestinal endoscopy overall more efficient.